PEMIKIRAN FILSAFAT ONTOLOGI TAN MALAKA DALAM MADILOG SERTA RELEVANSI DALAM BIDANG PENDIDIKAN - Fahriza, Ilham; Karneli, Yeni; Gusri Handayani, Puji (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study examines Tan Malaka's thoughts in Madilog, which asserts that the essence of reality is material and can be explained through rationality, natural law, and empirical evidence. Tan Malaka criticized mystical mindsets that were considered to hinder the development of science and national progress. Ontologically, his thinking is rooted in Marxist materialism, which views matter as the basis of all existence, including human consciousness. In contrast to Feuerbach's passive materialism, Tan Malaka emphasized the importance of human activity (work) as a practical force capable of driving social change. Thus, Madilog is an attempt to reconstruct the way of thinking of Indonesian society towards a scientific, logical, and critical mindset as a foundation for intellectual development and national progress.